Designing Interactive Media for the Introduction of Visual Language on Kresnayana Relief in Prambanan - Supandi, Fajar Persada (Universitas Negeri Medan, 2024)
Prambanan Temple in Yogyakarta is one of Indonesia's most meaningful and historic cultural heritages. One of the most impressive elements of the temple is the Kresnayana Relief, which depicts the epic story of Lord Vishnu transforming into Kresna. This relief has high artistic and historical value, but understanding and appreciation of the story is often limited. This research aims to design an interactive media that combines visual language with modern technology, focusing on the Kresnayana Relief. Through literature studies, surveys, interviews, and visual art analysis, we understand the story of the Kresnayana Relief and the interest of visitors to Prambanan Temple in interactive media. The result of this research is an interactive media prototype designed to provide an immersive experience in understanding the Kresnayana Relief story. The prototype includes a user-friendly interface, visual animation, narration, and audio elements that aim to enhance visitors' understanding and appreciation of this relief.